Compatible reuse of the single hall churches in Catania (IT): thinking and proposals - Alessandro Lo Faro; Attilio Mondello; Angelo Salemi (Vitruvio: International Journal of Architectural Technology and Sustainability, 2018)
Summarizing the most recent studies about scientific approaches to the theme of building reuse, we propose a metadesign strategy applied to the single hall churches in Catania’s historic centre. We have performed a census and analyses on them from a morphological, technical and thermo-physical point of view. We also conducted an analysis of the urban settlement system in which these historic buildings are located, in order to verify compatibility with the "new" potential uses. However, a critical issue emerges regarding the possibility to standardize the decision-making processes involving historic buildings with a high cultural relevance.